Incidence and Intensity of Smoothed Income Poverty in European Countries - Jan Goebel; Birgit Kuchler (Journal of European Social Policy, 2003)
The purpose of this paper is to obtain, by combining two longitudinal perspectives, a more detailed national picture of poverty in the member states of the European Union, using the first four waves (1994–7) of the European Community Household Panel (ECHP). In addition to this detailed consideration is given to the time dimension, poverty incidence, poverty gap and poverty intensity. Overall, the ranking across countries and dimensions is relatively robust. Denmark and Portugal differ from the rest of the countries in each dimension. Other exceptions include France and Ireland, where poverty intensity is considerably lower than in the other welfare regimes. The results in terms of the different subgroups of poor individuals, namely transitory, intermittently and persistently poor, emphasize the importance of a more differentiated perspective on poverty, in particular concerning the relationship between social and demographic characteristics and individuals' long-term income situation.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; ECHP; panel data; poverty; smoothed income